Levodopa-Responsive Early-Onset Parkinsonism in Down Syndrome. (15th February 2018) - Palat, Padmini; Hickey, Francis; Patel, Lina; Sannar, Elise
Abstract : Individuals with Down syndrome (DS) can develop Alzheimer's disease as early as 30 to 40 years old, but parkinsonism is rarely described. We report on a 20-year-old woman with Down syndrome and parkinsonism who responded dramatically to carbidopa-levodopa. We propose that the occurrence of parkinsonism in individuals with DS may be underreported. Recognizing and treating this condition may improve quality of life.